Fixation of Rotor Laminate in an Electric Machine - Nylander, Erik; Olson, Adam (My University, 2022)
In the future it is expected to exist twice as many cars on the roads as it does today. For companies manufacturing electric cars, such as Volvo Cars, hundreds of millions of traction motors must be produced. Therefore, an efficient and safe way of doing this is of great interest. Today, Volvo Cars assembles the rotor onto the shaft using a shrink-fit method where the rotor stack is heated and the shaft is cooled using liquid nitrogen. A new solution that can achieve the requests on the motor without using liquid nitrogen as cooling would simplify the assembly process, make it safer, and reduce the manufacturing costs. Alternative geometries to the regular circular shaft and rotor were investigated in this work by creating models using ANSA and analysing them with Abaqus. The geometry of the interference between shaft and rotor that was produced from this investigation is called valleys. It is based from the already existing shaft, but with circular cutouts around the outer edge. The cutouts are supposed to match a grinding tool to obtain a high manufacturability. The chosen solution was optimized against torque capacity, slip angle and fatigue life. The design is not final since the model has not yet been tested with any temperature gradient across the assemble, which may affect the contact between rotor and shaft. Real life testing is also necessary to ensure that the simulations are resembling the reality.
Keywords: Shrink fit; rotor; Laminate; Electric machine; Grip; Torque; Slip; Car; Finite element method